Global Tourism Watch 2011 - Canadian Tourism Commission; Destination Canada (Borealis, 2016)
The Canadian Tourism Commission (CTC) began conducting the annual Global Tourism Watch (GTW) program in 2007 to expand consumer-based intelligence in its core markets. In 2011, the fifth year of the program, the GTW was implemented in 12 markets – Canada, the US, Mexico, the UK, France, Germany, Australia, Japan, China, South Korea, Brazil and India. The 2011 research was co-funded by a regional partner group that included Alberta, British Columbia, Manitoba, Ontario, Québec, New Brunswick, Newfoundland and Labrador, Northwest Territories, Nova Scotia, Nunavut and Yukon. The GTW program was designed to monitor and report on key market indicators for Canada, track brand performance and examine Canada's market positioning over time, and across all core markets, in a consistent way. The overall objectives of the GTW study are to: monitor key performance indicators, track response to Brand Canada, identify and track product opportunities and provide input into strategic market plans.